Semiotic Analysis of Emojis in The Comments Section of Nasdaily’s Instagram - Mochammad Alvin Pratama Putra; Dwi Taurina Mila Wardhani; Yopi Thahara (English Journal Antartika, 2025)
This study investigates the semiotic meaning in which emojis are used in the comment section of Nas Daily's Instagram posts, an Israeli-Palestinian social media influencer. This study employs Saussure's (1959) theory of semiotics i.e., signifier and signified relationship and Evans's (2017) linguistic theory of emojis, discussing their affective and contextual roles in online communication. A qualitative descriptive design was followed, and data were collected from screenshots of emojis in comments on the Instagram post by Nas Daily on November 26, 2024, about the Nas Scholarship. Data analysis applied Spradley's (1980) four-stage model: Domain Analysis, Taxonomic Analysis, Componential Analysis, and Cultural Theme Analysis. Results show that emojis serve certain communicative functions, where the most frequent functions are Substitution and Reinforcement. The most commonly used emoji sets are People, Symbols, and Smileys. These allow individuals to express emotions, emphasize their messages, or even replace words themselves. The study finds that Instagram users typically use emojis to summarize and reinforce their messages, especially in favorable and supportive settings such as in Nas Daily's comments. Semiotically, emojis are unveiled to be endowed with rich meaning and potent visual means of communication, and using them contributes to social relationships' formation in virtual environments.